Genomic Evidence Suggests Viral Persistence of Sars-Cov-2 for 386 Days in Health Worker: A Case Report from Santiago of Chile - Sandino-Garcia, A; Imarai-Bahamonde, C; Maisey-Munoz, K; Acuna-Castillo, C; Valdes-Henriquez, D; Luraschi-Vargas, R; Barrera-Ávalos, C; Reyes-Lopez, F; Vallejos-Vidal, E; Inostroza-Molina, A (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The COVID-19 pandemic continues to affect several countries. One of the best ways to control its spread is the timely identification of infected patients for isolation and quarantine. While an episode of infection lasts an average of 8–10 days from the onset of symptoms, there is literature describing long-lasting viral persistence events. Here, we report a case of persistence of SARS-CoV-2 for 386 days in a health worker from Santiago de Chile. Our study could be one of the longest reported viral persistence events. RNA sequencing analyses indicated that the first positive diagnosis (8 June 2020) corresponded to a SARS-CoV-2 variant belonging to Clade Nextstrain 20A. Three hundred eighty-six days later (23 September 2021), the second positive result reached the same viral variant (Clade 20A) but without presence or circulation in Chile since May 2021. Both sequencing coverages showed an identity of 99.21%, with some mutations related to the severity of the disease (ORF1b:P314L) and more infectivity (S:D614G). This work reinforces the idea of implementing an RT-qPCR or rapid antigen test once the quarantine is fulfilled to ensure viral absence, identify potential persistence, and, consequently, minimize the risk of local outbreaks of SARS-CoV-2 infection. © 2022 by the authors.